Preparo de amostra empregando microextração líquido-líquido dispersiva em fase reversa em microtubos para determinação de lítio em graxas lubrificantes - Kusbiak, Ana Carolina Corrêa (2021)
Lithium is a metal that has been used in several branches of technology, given its multiple applicability. Extracted from lithium hydroxide, lithium in automotive lubricating grease is one of the derivatives of this element. Quality control of this grease is an important step to ensure its functionality. In the present work, the use of a sustainable Reverse Phase Liquid-Liquid microextraction - RP-DLLME methodology was evaluated, using miniaturization with microtubes for the determination of lithium in different brands of automotive lubricating greases. The study aims to introduce an environmentally viable methodology in the analysis of lubricating grease, contributing to the monitoring of quality control and prolonging its useful life. Initially, the volume of sample mass sufficient for recovery, the solvents propanol and isopropanol as dispersers, the concentration of the extracting solvent HNO3 (0.0, 0.25; 0.50; 1.00; 2.00; 3,00, 4.00 mol L-1) and the proportion of isopropanol at the junction of the solvents (50:50; 60:40; 70:30 and 80:20 (v/v)), as well as the volume of the dispersing/extracting solvent solution inserted (250; 500 and 750 µL). The temperature in a water bath (60, 65, 70 and 75 ºC) and the centrifugation time (5, 10 and 15 min) were also tested. The reading of the samples was carried out using flame atomic emission spectrometry, with the aid of aqueous reference solutions prepared from a 1000 µL standard. This study showed that the miniaturized RP-DLLME methodology used is favorable to the analyte and the established conditions, as it brought good recovery results with little demand for time and reagents, showing recoveries of 89 to 101%. The technique, which is already considered sustainable, was miniaturized respecting the parameters of green analytical chemistry. At the end of the tests, seven different brands of lithium grease were analyzed, applying the technique.